Transfer Teknologi Pembuatan Pupuk Cair dari Sampah Organik Limbah Pertanian untuk Masyarakat Desa Pasar Melintang - Hendris Syah Putra; M. Fariz Afif Hasibuan; Heni Naura Putri Hendro; Tigor Gomgom Simamora (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – This community service program aims to transfer simple technology for producing liquid organic fertilizer (LOF) from agricultural organic waste to farmers in Pasar Melintang Village, Deli Serdang Regency, in order to improve waste management practices and support sustainable agriculture. Design/methodology/approach – The program was implemented through extension activities, hands-on demonstrations of LOF production using simple composters, mentoring, and fermentation monitoring for 14 days. Participants consisted of 20 farmers engaged in rice and horticultural cultivation. Evaluation was conducted by observing farmers’ participation, their ability to independently produce LOF, and the successful fermentation process. Findings – The results show a significant increase in farmers’ knowledge and skills in processing agricultural waste into liquid organic fertilizer. The produced LOF exhibited good fermentation characteristics and was applied to paddy and horticultural crops, improving plant growth and soil conditions. Farmers also reported reduced dependence on chemical fertilizers and lower production costs. Community participation and independent use of composters indicate the sustainability of the program. Originality/value – This program demonstrates the effectiveness of integrating simple composting technology with participatory empowerment approaches to promote circular agriculture at the village level. It offers a practical model for managing agricultural waste while enhancing farmers’ capacity and environmental awareness.